2023
DOI: 10.1002/acr.25057
|View full text |Cite
|
Sign up to set email alerts
|

Association of Change in Body Mass Index With Incidence and Progression of the Structural Defects of Hip Osteoarthritis: Data From the Osteoarthritis Initiative and the Cohort Hip and Cohort Knee study

Abstract: Objective To define the association between change in body mass index (BMI) and the incidence and progression of structural defects of hip osteoarthritis as assessed by radiography. Methods We used data from 2 independent cohort studies: the Osteoarthritis Initiative (OAI) and the Cohort Hip and Cohort Knee (CHECK) study. Our exposure was change in BMI from baseline to 4–5 years’ follow‐up. Our outcomes were the incidence and progression of structural defects of hip osteoarthritis as assessed using a modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…These findings add to growing evidence that weight loss has no benefit for hip osteoarthritis. We do not know of any randomized controlled trials that have investigated the effect of weight loss on hip osteoarthritis, but we know of 7 observational studies [16][17][18][19][20][21][22] that investigated the association of weight loss with hip osteoarthritis, in particular for structural defects of the hip joint, hip replacement, and hip pain. Of these 7 studies, 2 studies 18,22 found no evidence of an association between weight loss and structural defects of the overall hip nor defects in any individual structural features of the hip, and 4 studies [18][19][20][21] found no association with hip replacement (total and/or partial).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings add to growing evidence that weight loss has no benefit for hip osteoarthritis. We do not know of any randomized controlled trials that have investigated the effect of weight loss on hip osteoarthritis, but we know of 7 observational studies [16][17][18][19][20][21][22] that investigated the association of weight loss with hip osteoarthritis, in particular for structural defects of the hip joint, hip replacement, and hip pain. Of these 7 studies, 2 studies 18,22 found no evidence of an association between weight loss and structural defects of the overall hip nor defects in any individual structural features of the hip, and 4 studies [18][19][20][21] found no association with hip replacement (total and/or partial).…”
Section: Discussionmentioning
confidence: 99%
“…We do not know of any randomized controlled trials that have investigated the effect of weight loss on hip osteoarthritis, but we know of 7 observational studies [16][17][18][19][20][21][22] that investigated the association of weight loss with hip osteoarthritis, in particular for structural defects of the hip joint, hip replacement, and hip pain. Of these 7 studies, 2 studies 18,22 found no evidence of an association between weight loss and structural defects of the overall hip nor defects in any individual structural features of the hip, and 4 studies [18][19][20][21] found no association with hip replacement (total and/or partial). Of the 4 studies that investigated hip replacement, [18][19][20][21] only one study, 20 involving participants from the Osteoarthritis Initiative (OAI), followed up over 8 years, showed an association of weight loss with decreased risk of hip replacement, but only in participants who had hip pain at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations